Energy Loss at the Base of a Free Straight Drop Spillway - Salmasi, Farzin; Abraham, John (Current Overview on Science and Technology Research Vol. 6, 2022)
A vertical drop or free overfall is a common feature in both natural and artificial channels. Natural drops are formed by river bed erosion while artificial drops are built in irrigation systems to reduce the channel slope to designed slope. Greater energy dissipation drops occur in stepped spillways. The greater energy dissipation is caused by mixing of the jet with the pool at the downstream end of each drop. As a result, it will be the cause of the reduction in the energy dissipater that is generally provided in toe of drops and stepped spillways. In this study, the energy dissipation in straight drops is investigated by fabricating physical models. Effective geometric and hydraulic parameters are determined and three drops with different heights were constructed from plexiglas. These physical models were installed in two existing flumes in the hydraulic laboratory at university of Tabriz, Iran. Several runs of physical models were performed to determine the essential parameters for determining energy dissipation. The results reveal that energy dissipation in drops is affected by drop height and discharge. Predicted relative energy dissipation varied from 10.0% (for yc/h=0.94) to 94.3% (for yc/h=0.02). Energy loss caused by a drop is mainly due to the mixing of the jet with the pool behind the jet that causes air bubble entrainment in the flow. A statistical model was developed to predict the energy dissipation in drops that reveal nonlinear correlation between effective parameters. Comparisons between this study and results of Moore, Rand, White, Rajaratnam and Chamani, showed that White's model overestimates the energy dissipation in drops and Rand's model underestimates the energy dissipation in drops. The others can predict the energy dissipation similar to the proposed statistical model. The length of the downstream stilling basin predicted by White is 20% smaller than the others.